1991
DOI: 10.1007/bf02576682
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proliferation of coronary endothelial cells in response to growth factors is synergized by hemodialysate compounds in vitro

Abstract: Using capillary endothelial cells from the coronary system of guinea pig heart, we have devised an in vitro assay suitable for measuring proliferative and growth-promoting effects mediated by drugs and growth factors. In this assay, hemodialysate and fractions isolated from it--consisting exclusively of low-molecular-weight compounds from calf blood--stimulate the proliferation of coronary endothelial cells. This effect is not a trivial nutritive one. Furthermore, in respect to the stimulation of proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…For example, insulin stimulates DNA synthesis in bovine corneal [Feldman et al, 1993;Crow et al, 1994] and retinal [King et al, 1983] endothelium, but has no signi®cant stimulatory effect on endothelium derived from guinea pig coronary [Schonwald et al, 1991], human umbilical vein [Taggart and Stout, 1980;King et al, 1983] and bovine aortic [King et al, 1983] endothelial cells. King et al used Scatchard analysis to demonstrate capacity of 125 I-insulin to bind high-af®nity receptors on bovine retinal capillary endothelial and aortic endothelial cells [King et al, 1983], and suggested differences in the responsiveness of endothelial cells derived from capillaries and large vessels to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, insulin stimulates DNA synthesis in bovine corneal [Feldman et al, 1993;Crow et al, 1994] and retinal [King et al, 1983] endothelium, but has no signi®cant stimulatory effect on endothelium derived from guinea pig coronary [Schonwald et al, 1991], human umbilical vein [Taggart and Stout, 1980;King et al, 1983] and bovine aortic [King et al, 1983] endothelial cells. King et al used Scatchard analysis to demonstrate capacity of 125 I-insulin to bind high-af®nity receptors on bovine retinal capillary endothelial and aortic endothelial cells [King et al, 1983], and suggested differences in the responsiveness of endothelial cells derived from capillaries and large vessels to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Study has shown the drug to not contain peptide, growth factor or hormone-like substances [2]. Further, in vitro evidence suggests that Actovegin promotes oxidative metabolism and shifts the redox-balance of cells to produce more oxidized substrates, possibly protecting against hypoxic cell injury [2].…”
Section: In Vitro Evidencementioning
confidence: 99%
“…Study has shown the drug to not contain peptide, growth factor or hormone-like substances [2]. Further, in vitro evidence suggests that Actovegin promotes oxidative metabolism and shifts the redox-balance of cells to produce more oxidized substrates, possibly protecting against hypoxic cell injury [2]. This mechanism can be logically extrapolated to the first few hours of muscle injury where the goal of any therapeutic intervention would be to interrupt the process of cell damaging events, and therefore importantly preserve cell viability at the injury site.…”
Section: In Vitro Evidencementioning
confidence: 99%
“…The organic compounds of Actovegin do not exceed a molecular mass of 3 kD. The active fraction isolated from Actovegin contains predomi nantly oligosaccharides as evaluated by gel filtration, anion exchange chromatography, proteinase K diges tion and chloroform/methanol/HCl extraction [11].…”
Section: Hemodialysatementioning
confidence: 99%
“…Growth-promoting effects of hemodialy sate combined with growth factors for coro nary endothelial cells have been described [11], We previously demonstrated an en hanced expression of the receptor for the epi dermal growth factor (EGF) after a single Xray dose of 6 Gy [12]. Here we investigated the regulation of the EGF receptor (EGFR) in the absence or presence of Actovegin and after irradiation.…”
Section: Introductionmentioning
confidence: 99%